2016
DOI: 10.1002/pits.21944
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Attitudes and Prevalence of Bullying Bystander Behavior in Middle School

Abstract: Separate lines of research find that proaggressive attitudes promote peer aggression and that bystanders play a pivotal role in deterring or facilitating bullying behavior. The current study hypothesized that proaggressive attitudes in middle school would deter students from standing up to bullying and encourage them to reinforce bullying behavior. Middle school students (n = 28,765) in 423 schools completed a statewide school climate survey that included an aggressive attitudes scale and their bystander respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
3
17
0
1
Order By: Relevance
“…Grade 8 students reported higher constructive intervention than did grade 10 students. These results converge with previous studies that have shown younger adolescents are significantly more likely to help in bullying scenarios than are older adolescents (Allison and Bussey 2017;Datta et al 2016;Stevens et al 2000). Males in the study reported higher moral disengagement, cyberbullying perpetration, victimization, and aggressive intervention behaviours than did females.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Grade 8 students reported higher constructive intervention than did grade 10 students. These results converge with previous studies that have shown younger adolescents are significantly more likely to help in bullying scenarios than are older adolescents (Allison and Bussey 2017;Datta et al 2016;Stevens et al 2000). Males in the study reported higher moral disengagement, cyberbullying perpetration, victimization, and aggressive intervention behaviours than did females.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies in traditional bullying have found that females are more likely to defend victims than are males Reijntjes et al 2016;Salmivalli et al 1996;Trach et al 2010) and younger students are more likely to defend than are older students (Datta et al 2016;Stevens et al 2000). Findings on grade and gender effects for bystander intervention in cyberbullying have been inconsistent (Allison and Bussey 2017;Barlińska et al 2013;Caravita et al 2012;Datta et al 2016;Macháčková et al 2013;Van Cleemput et al 2014). This inconsistency may be due to the increased anonymity of the cyber context, as adolescents perceive less pressure to exhibit age and gender-typical behaviours than in traditional bullying contexts.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A significant number of students witness bullying at school, with estimates ranging from 70-88% (Rivers, Poteat, Noret, & Ashurst, 2009). Findings indicate that of the 55% of students in a recent study classified as bystanders (i.e., students who witness bullying, do not engage in bullying, and are not victims), 46% do nothing to intervene (Datta, Cornell, & Huang, 2016). This finding is important because when students intervene and/or console the victim, acting as "defenders" (Salmivalli, Lagerspetz, Björkqvist, Ősterman, & Kaukiainen, 1996, p.15), bullying behavior decreases (Padgett & Notar, 2013;Salmivalli, 2014).…”
Section: A Bystander Approach To Interventionmentioning
confidence: 90%
“…Sejauh ini lebih banyak literatur yang membahas peran defender dan mengaitkannya dengan karakteristik individual (Datta, Cornell & Huang, 2016;Jenkins, Demaray, Frederick, & Summers, 2016), hubungan dengan teman sebaya (Gini, Pozzoli & Bussey, 2014;Van der Ploeg, Kretschmer, Salmivalli & Veenstra, 2017), dan konteks sekolah (Jungert et al, 2016;Storer, Casey, & Herrenkohl, 2017). Penelitian sebelumnya telah meneliti hubungan antara peran orang tua maupun empati terhadap peran defender, namun belum ada studi yang secara langsung mengaitkan melalui proses mediasi empati terhadap hubungan antara keterlibatan orang tua dan peran defender terutama pada usia remaja awal.…”
Section: Menurutunclassified